"I have visited the Chauvet Cave": the heritage experience of a rock art replica. Issue 2 (1st February 2020) - Duval, Mélanie; Smith, Benjamin; Gauchon, Christophe; Mayer, Laura; Malgat, Charlotte
ABSTRACT: Immersive digital technologies and 3D models are changing the way in which archaeology and heritage are presented to the public. Here we consider the role of physical 3D replicas and the values they hold vis-à-vis digital reproductions. We begin with a consideration of conceptions of 'real' versus 'fake' and the evolving history of academic notions of 'authenticity'. Then we explore a particularly significant recent case study, the creation of the replica known as the Cave of Chauvet 2, France. We discuss the choices underlying its construction, its selected characteristics and the intended experience that is offered to visitors. Our aim is to consider the manner in which visitors perceive the replica. Our research findings are based on interviews conducted with visitors and staff at the Cave of Chauvet 2 and observations of visitor management at the site (2016, 2017). We focus our discussion around the visitor experience of authenticity, the extent to which the replica has proven able to stand in place of the original. Our results proved surprising: over 90% of visitors gained an authentic heritage experience and, for many, the replica created a state of hyperreality in which they subconsciously meshed reality with simulation.